"BLANC A NOIR" Ready to Wear Fashion Design Inspired by the Paprikas’s Art Installation Design, "Trous de Memoire (Memory Holes)" - Maria, Anna; Aryani, Dewi Isma; Janty, Tan Indra (VCD, 2019)
This “BLANC À NOIR” ready to wear collection is inspired by the Paprika Design’s installation art, “Trous de Mémoire (Memory Holes)”. This installation was installed at Aires Libres for 1 month on September 2013. There are 6 large scale light boxes. It invites the viewers to walk down a memory lane, but there are tricks and humorous discoveries to be made, indicating that what is forgotten is not always lost. This collection is adapting the rectangular shape of the installation as the silhouette, the installation’s colors, black and white, and Trous de Mémoire Installation Art’s pictures and writings motif as a reference to make every looks. Also, adjusted with Trend Forecasting Grey Zone 2017-18 theme Vigilant and sub theme Structural-Cermat Terukur-Ekspos Teknik Sambung. The Target market are women with age range 27-35 years old, live in Bandung, Yogyakarta, and Jakarta, artistic, like visiting art event in Indonesia, a public figure and fashion trendsetter.